Characterising the nature of diffusion via a new indicator: Microcylinder and microring electrodes - Le, H; Kätelhön, E; Compton, R (Elsevier, 2019)
An indicator to character diffusion is introduced to quantify the extent of linear and convergent diffusion in chronoamperometric currents. Simulated data for microcylinder and microring models is thus characterised and different time scales of diffusive fluxes from different spatial locations are revealed and discussed. Finally, the applicability of the Aoki equation [Journal of Electroanalytical Chemistry, 186, 79 (1985)] to the chronoamperometric currents for various cylinder-like models is explored and assessed.